Odpowiedzi

Najlepsza Odpowiedź!
2010-01-21T20:30:18+01:00
(2x -7)² =4x²-49
(-3x - 2y)² =9x²-4y²
(-5a -2 jedna druga)² =25a²-6,25
(0,3x - 7)² =0,09x²-49
(2,3 - x )² =5,29-x²
(x² - 1)² =x⁴+1
2010-01-21T20:30:47+01:00
(2x -7)² =4x²+49
(-3x - 2y)² =9x²+4y²
(-5a -2 jedna druga)² =10a²+6jedna czwarta
(0,3x - 7)² =0,09+49
(2,3 - x )² =5,29+x²
(x² - 1)² =2x²+1

proszee ; )

do jestemszalona:
jak się mnoży minus z minusem to wychodzi plus ; )
2010-01-21T20:37:25+01:00
(2x-7)² = 4x² + 49
(-3x - 2y)² = 9x² + 4y²
(-5a - 2 ½)² = 25a² + 1¼
(0,3x - 7)² = 0.09x² + 49
(2,3 - x)² = 5,29 + x²
(x² + 1)² = x⁴ + 1